2020
DOI: 10.1080/25785826.2019.1710079
|View full text |Cite
|
Sign up to set email alerts
|

Clinical usefulness of anti-M-type phospholipase-A-receptor antibodies in patients with membranous nephropathy and the comparison of three quantification methods

Abstract: 2020) Clinical usefulness of anti-M-type phospholipase-A-receptor antibodies in patients with membranous nephropathy and the comparison of three quantification methods, Immunological Medicine, 43:1, 47-56,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 22 publications
3
10
0
Order By: Relevance
“…Serum albumin and urinary protein are generally used to quantitatively evaluate the severity of nephrotic syndrome in MN, which are important indicators for assessing disease activity ( Kanigicherla et al, 2013 ; Lin et al, 2015 ; Gopalakrishnan et al, 2016 ; Li et al, 2016 ). Consistent with data from aforementioned studies ( Li et al, 2016 ; Song et al, 2018 ; Provatopoulou et al, 2019 ; Katsumata et al, 2020 ; Li et al, 2021 ), we found a significant association of PLA2Rab with urinary protein and serum albumin indicating the correlation between antibody levels and disease activity ( Mahmud et al, 2019 ; Gong et al, 2020 ; Guo et al, 2020 ). However, Jullien et al (2017 ) claimed that the initial PLA2Rab level did not relate to the degree of proteinuria.…”
Section: Discussionsupporting
confidence: 91%
“…Serum albumin and urinary protein are generally used to quantitatively evaluate the severity of nephrotic syndrome in MN, which are important indicators for assessing disease activity ( Kanigicherla et al, 2013 ; Lin et al, 2015 ; Gopalakrishnan et al, 2016 ; Li et al, 2016 ). Consistent with data from aforementioned studies ( Li et al, 2016 ; Song et al, 2018 ; Provatopoulou et al, 2019 ; Katsumata et al, 2020 ; Li et al, 2021 ), we found a significant association of PLA2Rab with urinary protein and serum albumin indicating the correlation between antibody levels and disease activity ( Mahmud et al, 2019 ; Gong et al, 2020 ; Guo et al, 2020 ). However, Jullien et al (2017 ) claimed that the initial PLA2Rab level did not relate to the degree of proteinuria.…”
Section: Discussionsupporting
confidence: 91%
“…For example, only 24-hour urinary protein positively correlated with anti-PLA2R, while albumin, serum creatinine and CysC did not correlate in the study by Li et al [ 19 ]. In two Japanese studies, anti-PLA2R negatively correlated with albumin, but its correlations with serum creatinine and 24-hour urinary protein differed between the two studies [ 21 , 22 ]. The study by Hofstra et al [ 17 ] was consistent with our research on these correlations.…”
Section: Discussionmentioning
confidence: 99%
“…Although Greece also belongs to Europe, the sensitivity in a Greek population was only 48.48% [ 16 ]. In two studies of the Japanese population, the sensitivities were similar, 50.00% and 52.17%, and the specificities were both 100.00% [ 21 , 22 ]. China held four studies, with sensitivities of 62.20%, 60.17%, 50.88%, and 67.26%, and the specificities were all more than 90% [ 19 , 23 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…To clarify this important issue and in order to harmonize anti-PLA2R antibody results (thereby correctly assessing anti-PLA2R antibody prevalence in iMN), we reviewed several studies reporting the diagnostic accuracy of anti-PLA2R antibodies using the same ELISA (the only one commercially available), with a cut-off of 20 RU/ml, or 14 RU/ml, or 2.00 and 2.7 RU/ml. At 20 RU/ml, the average sensitivity was 65.5% with 98.4% specificity [12,17,20,21,24,25]. At a cut-off value of 14 RU/ ml, average sensitivity and specificity were 69.1% and 95.2%, respectively [12,20,26,27].…”
Section: Discussionmentioning
confidence: 94%